A produção do conhecimento nos centros federais de educação tecnológica - Leopoldo Gil Dulcio Vaz (1993)
This study analyzes the characteristics of the faculty of the Federal Centers for Technological Education in Brazil as users and producers of information, including their behavior during search and use of information, and how they disseminate their scientific and technical production. The instrument for data collection was a questionnaire. The results show that the teachers/researchers present a profise similar to that of the faculty of Brazilian universities. Their behavior during searchfor information was verified through the use of the critical incident technique. Information flows equally through formal and informal Channels, but the motivation to use formal sources is inhibited by the obsolescence of library Collections. Informal communication is poor, as well as within the centers as outside them. The results also reveal problems withih the information systems and small stimuli for research, as verified through the statistioal analysis of the productivity of the faculty and through their opinions. The internal causes for low productivity, as expressed by the respondents, are lack of institutional support and lack of funding. External factors are isolation of the teachers, possibly because they deal only with technical research (which does not favor discussions with colleagues) or because there are no other researchers in their specialties. The Federal Centers for Technologial Education Should promote and Consolidade research groups in Certain areas of study, as well as their informal Channels of Communication. There is also need tofind an equilibrium between teonical and academic tasks, to avoid damage to the quality of teaching provided to future researchers.